Validity of the Wide-range Assessment of Vision-related Essential Skills in Japanese Children with Learning Problems. - Okumura, Tomohito; Miura, Tomoko; Nakanishi, Makoto; Fukui, Miho; Toshikawa, Mari; Shimakawa, Shuichi; Wakamiya, Eiji; Tamai, Hiroshi; Ashida, Akira (Optometry & Vision Science, 2020)
Significance: Our study revealed that the validity of a new Japanese visual-perceptual test was acceptable. Visual-perceptual abilities are important to activities of daily living; thus, accurate assessment of visual perception is especially important for children with neurodevelopmental disorders and particularly so for those with learning problems.Purpose: Visual perception refers to the process by which one receives visual information through sensory impulses and then translates those impulses into meaning based on a previously developed view of the environment. A problem in Japan is the paucity of visual perception tests that use normative data from children who are native Japanese. The Wide-range Assessment of Vision-related Essential Skills (WAVES), which measures visual perception and eye-hand coordination skills and is based on Japanese normative data, was recently published in Japan. The validity of this test has not been comprehensively established.Methods: To investigate the validity of the WAVES, we used the Pearson correlation coefficient to calculate the degrees of association among WAVES scaled and index scores compared with Developmental Test of Visual Perception, Third Edition, scores from 108 elementary school children with symptoms of learning problems. Participants were recruited at Osaka Medical College Learning Disability Center and Sakai Seikeikai Learning Disability Center.Results: The concurrent validity of the WAVES was supported by moderate correlation (r = 0.67, P < .01) between the total scores for visual perception and eye-hand coordination index from the WAVES and general visual perception index from the Developmental Test of Visual Perception, Third Edition, even though a correlation analysis of subtests found differences between the two tests.Conclusions: Our results showed that the indices from the two tests measured nearly the same underlying visual-perceptual constructs and indicated that the WAVES had acceptable levels of concurrent validity.